Passengers and Crew's Evacuation from Passenger Ships Under Fire: An Agent-Based Model Simulation Study - Ahmad Firdhaus; Imam Pujo Mulyatno; Muhammad Luqman Hakim; Zen Zen (Department of Naval Architecture - Diponegoro University, 2023)
The characteristics of the passengers have a significant impact on how the evacuation procedures are carried out. During an evacuation, the amount of time it takes depends on how quickly passengers move. There is a correlation between age and travel speed, but not always. As a result of this problem, a significant number of passengers were unable to make it to the assembly point in time for the evacuation, which may have resulted in fatalities. An evacuation simulation will be carried out aboard passenger ships in the event of a fire. This research will employ agent-based modeling to perform the simulation, and it will include modifications for day and night, as well as for the number of emergency stairs used. The findings of this study are the simulation times for the evacuation of passengers and crew for each scenario, with the shortest time for evacuation occurring during the daytime with operational emergency stairs, clocking in at 36.51 minutes, and the longest time for evacuation occurring during the night with damaged emergency stairs, clocking in at 47.43 minutes. Both times are given in minutes. According to the findings, the evacuation circumstances satisfied the standards set by the IMO, which demanded that the entire amount of time spent evacuating be less than or equivalent to sixty minutes